Study on the environmental efficiency of agricultural water resources about typical cropping patterns around the Dongting Lake area. Issue 10 (3rd October 2022) - Yang, Yumei; Deng, Zhenghua; Lu, Xianming; Gao, Xiaoling
Abstract: This paper aims to evaluate the environmental efficiency of agricultural water resources utilization in different cropping patterns in the Dongting Lake area. To achieve that, the following materials are used: (1) study area: 16 counties (cities and districts) of Yueyang, Changde, and Yiyang around the Dongting Lake area; (2) data: relevant indicators of economic and environmental benefits of agricultural water resources utilization from 2011 to 2020; and (3) model: the Luenberger productivity model based on the directional distance function. With all the materials above, this paper calculates the environmental efficiency of typical cropping patterns in the Dongting Lake ecological zone and explores the spatial and temporal evolution patterns of typical cropping patterns in the lake area. The results show that (1) the environmental efficiency (LEI) of four typical cropping patterns in 16 counties (cities and districts) around Dongting Lake shows an overall increasing trend from 2011 to 2020, especially the environmental efficiency of four cropping patterns has increased significantly since 2014. (2) Among the four typical cropping patterns, the environmental efficiency of one-season rice + lobster is higher, and the environmental efficiency value of two-season rice + winter leisure is lower but most significantly improved. (3) The environmental efficiency of agricultural water resources in the hilly areas around the lake is higher than that in the Dongting Plain. Finally, some countermeasures and suggestions were put forward, such as implementing the reduction and efficiency of pesticide and chemical fertilizer in the planting industry in the lake area, optimizing the rice + planting mode, strengthening the construction of water conservation projects in the four river basins, and promoting high-standard farmland water-saving irrigation. HIGHLIGHT: To improve the efficiency of agricultural water resources and environmental use, establish an index system for the economic and environmental benefits of agricultural water resources use in the lake area. Application of the Luenberger productivity model based on the directional distance function to calculate the environmental efficiency of typical cropping patterns in the ecological zone around Dongting Lake. To explore the spatial and temporal evolution of the environmental efficiency of typical cropping patterns in the lake area, and to propose a series of countermeasures for the cropping industry in the lake area.